READING IN STUDENTS DURING TEXTUAL ANALYSISAS A MEANS OF DEVELOPING CULTURE - Amirkulovna, , Turakulova Okila (International Journal of Psychosocial Rehabilitation, 2020)
–Day and night the world analyzes news and information. The analysis of information, news, especially in the field of socio-political, economic, military, sports, and cultural life is not stopped. Eventually, news, news or misfortune that is happening anywhere in the world is spread over the world through the media and the Internet. Thinking speed, breadth, clarity, and content are important factors in this process. The flow of ideas is increasing, different relationships are expressed. All information and messages are perceived through reflection. The analytical conclusions of people with advanced thinking are clear and meaningful, avoiding mistakes and errors. Consumers’ opinions on the content of a single piece of information are very common in practice. Someone gives a biased analysis of what has happened and draws the wrong conclusions, while others look at the object of analysis from different angles and make an objective decision. Analytical thinking, knowledge and skills of the analyst is a key factor in the correct and accurate performance of the analysis. Through the analysis, the subject is investigated, disclosed in different ways, problems and their causes are identified, and optimal solutions are developed. Analysis is the most reliable way to know.